Pengaruh Inovasi Kurikulum dalam Kemajuan PAI di Pondok Pesantren - Hanafi, H. Hanif; Adin, Ahmad Muchlis (Lembaga Yasin AlSys, 2024)
Curriculum is one of the important elements in education. It contains lesson content and other things needed in the teaching and learning process in an educational institution. Islamic boarding schools are one of the Islamic religious educational institutions which of course use an educational curriculum in them. Along with developments in time and technology, curriculum innovation is needed to create a generation that has the skills and knowledge needed to contribute actively to modern society.